The Use of Hypertonic Saline and Hetastarch in an American Kestrel (Falco sparverius) with Traumatic Brain Injury - Rivas, Anne; Whittington, Julia; Emerson, Jessica (Wildlife Rehabilitation Bulletin, 2011)
An adult male American kestrel was presented to the Wildlife Medical Clinic at the University of Illinois by a motorist that witnessed the bird collide with a car. On presentation the kestrel was quiet, alert, responsive, and able to fly. However, over the next two hours the bird became obtunded, laterally recumbent, and lacked a pupillary light reflex in the left eye. Intravenous catheterization was performed and a bolus of hypertonic saline with hetastarch was administered to combat suspected increased intracranial pressure. The bolus was repeated during the first 12 hours. Additional therapy included administration of an anti–inflammatory agent, subdued lighting with minimal stimulation, and oxygen therapy. After two days the bird began to perch, and by five days the left eye was assessed as visual again. By day seven, the patient was deemed recovered, and was subsequently transferred to a raptor rehabilitation facility to recondition prior to release. This case suggests the usefulness of hypertonic saline with hetastarch as a treatment for traumatic brain injury in a wildlife rehabilitation setting.